Completeness of Medical Record Documents for Inpatient Kidney Failure at the Hospital - Tasya Aisyah Adinda Raekha; Sri Wahyuningsih; Nor Akmar Bt Mohd Yahya (Global Health Science Group, 2022)
Health service providers are required to record all services provided to patients in the form of a complete medical record file. Incomplete filling of medical records can lead to misinformation used by health professionals in providing services or treatment plans. This study aims to determine the completeness of medical record documents and the factors that cause incomplete medical record documents for kidney failure.This research is a literature study. The sample in this study were 5 journals related to the completeness of medical record documents for inpatient cases of kidney failure using purposive sampling technique. The instrument in this study used the google application. Processing of data by searching on the site, collecting overall journals, journal screening and extracting data based on inclusion criteria using the Systematic Literature Review (SLR) method. The analysis was carried out using data analysis techniques, namely quantitatively. The results of the study on the completeness of medical record documents for inpatient kidney failure based on a review of patient identification, the entire journal was incomplete, 100% incomplete, mostly on the name and age items. Review reporting there is 1 journal is 100% complete, 4 journals are not complete 100% incomplete mostly on date and time items, authentication review the entire journal is not complete. 100% of the incompleteness is found in the items of the doctor's name and the doctor's signature. The review of the recording of the entire journal is not complete. 100% of the incompleteness is on the item using the fixed line on the blank form. The factor of the incompleteness of the medical resume on the inpatient document is due to the lack of accuracy of the officers infilling, lack of discipline of officers, and the absence of a clear SOP. The conclusion of this study is that from 5 journals regarding the completeness of medical record documents in terms of reviews of identification, reporting, authentication and recording, it shows that medical record documents are 100% incomplete. This is due to the lack of accuracy of officers in filling it out, lack of discipline of officers, and the absence of clear SOPs.